Hyaluronic acid-alendronate conjugate: A macromolecular drug delivery system for intra-articular treatment of osteoarthritis. Issue 2 (June 2021) - Pluda, Stefano; Beninatto, Riccardo; Soato, Matteo; Barbera, Carlo; di Lucia, Alba; Fassina, Lidia; Gatti, Filippo; Guarise, Cristian; Galesso, Devis; Pavan, Mauro
Abstract: Objective: Osteoarthritis (OA) is a painful degenerative disease of the whole joint structure, including articular cartilage, synovial fluid, and subchondral bone. Hyaluronic acid (HA), an anionic non-sulfated glycosaminoglycan, is commonly used for intra-articular (IA) treatment in OA, while bisphosphonates (BPs) are anti-resorptive drugs that act on the bone. Here, a novel conjugate with a covalent and hydrolysable linker between HA and alendronate (ALD) was designed as an attractive therapeutic strategy for IA drug delivery. Design: The HA-ALD derivative was synthesized and tested in comparison with a simple mixture of HA and ALD for in vitro ALD release, rheological properties, cytotoxicity towards osteoblasts and chondrocytes and in an in vitro efficacy assay of OA inflammatory model on bovine cartilage explants. Results: The structure of HA-ALD was elucidated exhibiting no depolymerization and efficient drug incorporation. The controlled ALD release in vitro was slower compared to the simple mixture of HA and ALD; moreover, the derivative showed calcium-tuned rheological properties. The absence of cytotoxicity towards osteoblasts and chondrocytes was shown for up to 7 days, and the viability of chondrocytes was confirmed by fluorescence microscopy. Finally, a reduction in collagen release and MMP-13 expression was measured in the OA inflammatory model. Conclusion: This new HA-ALD derivative opens the door to a new approach for OA treatment, as it combines viscosupplementation and biological effects of HA with the pharmacological activity of BPs. Prolonged ALD release increased rheological properties and beneficial effect against cartilage degradation make it a promising IA therapy for OA. Graphical abstract: Image 1 Highlights: Development of an IA treatment to target OA pathogenesis rather than symptoms. A novel hyaluronan-alendronate conjugate was synthesized with a reversible linker. The drug delivery system confirmed slow alendronate release. The efficacy was demonstrated in an osteoarthritis inflammatory model. New intra-articular treatment: viscosupplementation and pharmacological activity.